Peningkatan Literasi Digital Marketing Dalam Mengembangkan Usaha Mikro Berbasis Online Bagi Masyarakat Desa Bukit Makmur Kecamatan Pinang Raya Kabupaten Bengkulu Utara - Malau, Joyana Uliarta; Soleh, Ahmad; Suwarni, Suwarni; Febliansa, Muhammad Rahman; Hardinata, Dodi (Universitas Dehasen Bengkulu, 2025)
Increasing digital marketing literacy is a strategic step to develop the digital transformation of Micro, Small and Medium Enterprises (MSMEs) in the community of Bukit Makmur Village, Pinang Raya District, North Bengkulu Regency. This program aims to improve the ability of MSMEs to utilize digital platforms to expand market reach and competitiveness. Improving digital literacy refers to a systematic effort to strengthen an individual's ability to access, understand, evaluate and utilize digital information effectively and responsibly. This includes mastery of information and communication technology (ICT) skills, an understanding of digital ethics, and the ability to think critically in dealing with a variety of digital content that continues to evolve.The activities were implemented through digital literacy training, website development, and intensive mentoring. As a result, the MSMEs involved showed significant improvement in understanding and implementing digital marketing, including optimizing social media and websites, which contributed to increased sales. In addition, the program built students' competencies in the application of digital technology and collaboration. In conclusion, collaboration between universities, students, and MSMEs can create innovative solutions that support the local digital economy, while providing opportunities for MSMEs to compete in a wider market.